PENDIDIKAN ISLAM DAN HAK PENYANDANG DISABILITAS; SUATU PANDANGAN KOMPREHENSIF DAN INTEGRATIF - Ukhtul Iffah; Hasanah Hasanah; Baitur Rahman (Fakultas Tarbiyah, Universitas Ibrahimy, 2021)
Abstract: education is an effort made consciously and systematically to empowering all of the potential students to become complete human beings. the implication of education for society is being independent. therefore education is too important on the side of the community and it is increasingly difficult to leave it. independent society is a society that can supply all of their life necessities without depend on whatever. a lot of literature discusses moral decadention, so that necessary to socialize Islamic education massively to minimize moral decadention. on the other aspect, education is right of humans, including children with special needs. people with disabilities should not be underestimated by everyone, in Islamic religion never discriminate human existence based on physically, psychically, tradition, and other aspects except submission to Allah SWT. Keywords: Islamic Education, Disability Rights